Oral Capecitabine Achieves Response in Metastatic Eccrine Carcinoma - Kristian Larson; Hani M. Babiker; Andrew Kovoor; Joy Liau; Jordan Eldersveld; Emad Elquza (Case Reports in Oncological Medicine)
The low prevalence rate and limited literature on eccrine carcinoma (EC) pose a challenge to properly diagnosing and treating this rare malignancy. EC lesions tend to present similarly to other cutaneous neoplasms and dermatitis-like conditions. Efficacious treatment guidelines have not been established for patients diagnosed with EC, and few treatment regimens have demonstrated clinical benefit. Due to the high metastatic potential of EC, recognizing the clinical presentation, properly diagnosing, and utilizing beneficial treatment options are important for managing this disease. We report a case of a 66-year-old female who presented with lesions that her primary care provider misdiagnosed as basal cell carcinoma. The disease responded poorly to taxane- and platinum-based chemotherapies as well as an isolated limb perfusion of an alkylating agent. However, continuous dosing of oral capecitabine achieved an 18-month period of progression free survival (PFS) and ameliorated quality of life. We wish to highlight this rare disease and discuss presentation, diagnosis, and management as it is most often misdiagnosed leading to advanced metastatic disease when patients present to the oncologist. In addition, it is crucial to study and report potentially efficacious regimens considering the lack of clinical trials in this disease.